Recent Time Trends in the Epidemiology of Stage IV Prostate Cancer in the United States: Analysis of Data From the Surveillance, Epidemiology, and End Results Program* - Cetin, Karynsa (Urology, 2009)
OBJECTIVES: To describe recent epidemiologic trends in stage IV prostate cancer. Although advances in screening and diagnostic techniques have led to earlier detection of prostate cancer, a portion of patients still present with late-stage disease. METHODS: Population-based cancer registry data from the Surveillance, Epidemiology, and End Results Program (cases from 1988 to 2003, follow-up through 2005) were used to calculate annual age-adjusted incidence rates of stage IV prostate cancer (overall and for the subset presenting with distant metastases) and to assess time trends in patient, tumor, and treatment characteristics and survival. RESULTS: From 1988 to 2003, the age-adjusted incidence of stage IV prostate cancer significantly declined by 6.4% each year. The proportion of men diagnosed at younger ages, with poorly differentiated tumors, or who underwent a radical prostatectomy significantly increased over time. Five-year relative survival improved across the study period (from 41.6% to 62.3%), particularly in those diagnosed at younger ages or with moderately to well-differentiated tumors. Later years of diagnosis were independently associated with a decreased risk of death (from all causes and from prostate cancer specifically) after controlling for important patient, tumor, and treatment characteristics. Tumor grade and receipt of radical prostatectomy appeared to be the strongest independent prognostic indicators. Temporal trends were similar in the subset presenting with distant metastases, except that no significant improvement in survival was observed. CONCLUSIONS: As younger men may expect to live longer with advanced prostate cancer, there remains a need to widen the range of therapeutic and supportive care options.